Validez y confiabilidad de la versión en español de la escala multidimensional de la UNESP-Botucatu para evaluar el dolor postoperatorio en gatos - Brondani, Juliana Tabarelli [UNESP]; Luna, Stelio Pacca Loureiro [UNESP]; Crosignani, Nadia; Redondo, José Ignacio; Granados, María del Mar; Bustamante, Hedie; Palacios, C.; Otero, Pablo (Univ Austral Chile, Fac Ciencias Veterinarias, 2014)
This study focused on the validation of the Spanish version of the UNESP-Botucatu multidimensional composite pain scale to assess postoperative pain in cats. The original scale in Portuguese was translated into Spanish by two independent translators, and summarised in one version by a third individual. The summarised version was back-translated and minor adjustments were made. The scale was reviewed by three anesthesiologists with Spanish as their first language, and the final version was submitted to psychometric testing. Thirty cats undergoing ovariohysterectomy were video recorded during the perioperative period. Six observers from different spanish speaking countries, who had Spanish as the first language watched the videos and determined the pain scores using the Spanish version of the scale, identifying the cats that should receive analgesics. Videos were reanalysed in a different order about 2 months after the first assessment. The sensitivity to change, content and construct validity were established by the significant change in pain scores in response to surgery and analgesics. The agreement between the evaluations of the 'gold standard'(researcher that developed the scale) and the other observers confirmed the criterion validity. Inter- and intra-rater reliability, evaluated by intra-class correlation coefficient, ranged from good to very good for all scale items. The cut-off point for rescue analgesia identified by Receiver Operating Characteristic curve was > 7 with 92% of sensitivity and 91% of specificity. The Spanish version of the UNESP-Botucatu multidimensional composite pain scale is interpretable (has an optimal analgesic intervention score), valid and reliable instrument for assessing acute pain in cats undergoing ovariohysterectomy.

El objetivo de este estudio fue validar la versión en español de la escala multidimensional de la UNESP-Botucatu para evaluar el dolor postoperatorio en gatos. La escala original en portugués se tradujo al español y una versión sintetizada fue retrotraducida tras realizar pequeños ajustes. Tres anestesiólogos revisaron la escala (español de lengua materna), y la versión final se sometió a test psicométricos. Treinta gatas sometidas a ovariohisterectomía fueron filmadas durante el periquirúrgico. Seis observadores de diferentes culturas y con el español como lengua materna evaluaron los videos determinando las puntuaciones de dolor utilizando la escala en español, identificando a los animales que debían recibir analgesia adicional. Los videos se reevaluaron aproximadamente dos meses después del primer análisis. La sensibilidad al cambio, validez del contenido y constructo del instrumento se establecieron gracias a las alteraciones significativas en las puntuaciones de dolor en respuesta a la cirugía y analgesia. La concordancia entre las evaluaciones del patrón de referencia (investigador que desarrolló la escala) con los demás observadores confirmó la validez de criterio. La confiabilidad inter e intraobservadores evaluada mediante el coeficiente de correlación intraclase varió entre buena y muy buena en todos los ítems de la escala. La puntuación para intervención analgésica, identificada por la curva Receiver Operating Characteristic, fue de > 7 con una sensibilidad del 92% y una especificidad del 91%. La versión en español de la escala multidimensional de la UNESP-Botucatu es un instrumento interpretable (presenta una puntuación para intervención analgésica), válido y confiable para evaluar el dolor agudo en gatas sometidas a ovariohisterectomía.
Validation of the spanish version of the UNESP-Botucatu multidimensional composite pain scale to assess postoperative pain in cats
Keywords: Cats; Pain; Validation; Scale; Gatos; Dolor; Validación; Escalas